A study of áv2ñ with NeXSPheRIO - Andrade,R. P. G. (2007)
Elliptic flow at RHIC is computed event by event with NeXSPheRIO. Reasonable agreement with experimental data on v2(eta) and v2(pt) is obtained. Various effects are studied as well: equation of state (with or without critical point), emission mechanism (Cooper-Frye prescription or continuous emission), type of the initial conditions (average or fluctuating initial conditions).